Approximation by rational functions on doubly connected domains in weighted generalized grand Smirnov classes - Testici, A. (Ukrains’kyi Matematychnyi Zhurnal, 2021)
UDC 517.5Let $G\subset \mathbb{C}$ be a doubly connected domain bounded by two rectifiable Carleson curves. In this work, we use the higher modulus of smoothness in order to investigate the approximation properties of $(p-ε)$-Faber–Laurent rational functions in the subclass of weighted generalized grand Smirnov classes ${E}^{p),θ } ( {G,ω })$ of analytic functions.